Peran Kepala Madrasah Dalam Mengembangkan Kurikulum 2013 Pada Masa Covid 19: (Studi Kasus Di Mts Swasta Yaspen Muslim Pematang Tengah) - Usmaidar, Luthfi Amirah Nasution, As’ad Badar (Continuous Education: Journal of Science and Research, 2021)
Teacher performance needs to be improved and improved in connection with the current learning is carried out boldly. This type of research is descriptive qualitative using a field study approach (field research). Methods of collecting data by means of observation, interviews and documentation. The informants of this study were the head of the madrasa, teachers and students. Sources of data in two ways, namely primary sources and secondary sources. The conclusion in this study is that the role of the head of Madrasah in developing the 2013 Curriculum during the covid 19 pandemic at Islamic Islamic Junior High School Yaspen Muslim Pematang Tengah consists of three categories, namely: Implementing effective and meaningful learning which begins with planning, namely making syllabus and lesson plans and presenting student activities. Organizing learning includes socializing the 2013 curriculum, utilizing the environment for teaching and learning processes as well as developing Madrasah policies. learning is in accordance with the learning process using a scientific approach which consists of observing, gathering information, associating and communicating teaching and learning activities well.